Anti-glaucoma agents-induced pseudodendritic keratitis presumed to be herpetic simplex keratitis: a clinical case series - Huai-Lung Chang (Nature Portfolio, 2021)
Abstract Anti-glaucoma agents-induced corneal toxicity may be misdiagnosed as herpetic simplex keratitis (HSK). In our study, nineteen glaucoma patients were presumed to have HSK before referral. Corneal lesions were classified into (I) linear pseudodendritic lesions formed by elevated opacified cells, (II) linear pseudodendritic lesions formed by grouped superficial punctate keratitis (SPK), (III) satellite full-thickness epithelial defects, (IV) satellite lesions formed by elevated opacified cells, and (V) geographic lesions formed by grouped SPK. We observed thirty-one events, with 15 in the lower and 16 in the central corneas. There were 21 (67.7%) type II, five (16.1%) type V, two (6.5%) of each for types III and IV, and one (3.2%) type I events. Among linear lesions (types I and II), 17 (77.3%) had horizontal and 5 (22.7%) had curvilinear orientations. Exposure duration to the last-added anti-glaucoma agent was three days to 14.5 years. About half of the events (16/31, 51.6%) used prostaglandin analogues, and 30/31 (96.8%) applied benzalkonium chloride (BAK)-containing agents. All lesions resolved within two months after decreasing offending medications or enhancing protection of ocular surface. In conclusion, anti-glaucoma agents-induced pseudodendritic keratitis presents majorly in central-lower cornea as horizontally linear lesions, and BAK-containing agents are observed in the most events.